Gallstone and Diabetes Mellitus - Hery Djagat Purnomo; Hirlan Hirlan (The Indonesian Society for Digestive Endoscopy, 2008)
Diabetes Mellitus (DM) is a metabolic disease which has high prevalence among the population. The prevalence is increasing in accordance to life style changes in the society. Gallstone is frequently found in diabetic patients especially in women with type 2 DM. Nevertheless, studies on the prevalence of gallstone among diabetic patients population have shown inconsistent/contradictive results. Insulin resistance which is frequently found in type 2 DM patients is the underlying factor that correlates obesity, central adiposity, and low physical activity with gallstone disease. Two important physiological reasons in diabetic patients that may increase the risk of gallstone formation are: (1) Increased total cholesterol synthesis that causes bile becomes more easily transformed into cholesterol stone (lithogenic); (2) Diabetic patients have larger size and probably reduced motility of the gallbladder that cause increased formation of cholesterol crystals. However, recent study demonstrated that DM that merely exists without any contribution of other factors is not significant to increase the risk of gallstone formation. The gallstone management in diabetic patients is the same as the management in non-diabetic patients. Elective surgery with laparoscopic cholecystectomy is the treatment of choice for symptomatic cases. Drug treatment is indicated for patients with cholesterol stone, small stone (diameter 5 mm), and well-functioned cystic duct. Keywords: diabetes mellitus, gallstone, insulin resistance, cholesterol synthesis, motility, laparoscopic cholecystectomy